PERSON AND POLITICS IN INFORMATION AGE - Комарова, Т. Г. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The article deals with questions of human interaction and politics in information epoch. External conditions of human existence constantly change, presenting new challenges. For individual and society as a whole, it is necessary to adapt dynamically. Processes of mutual influence of technical, technological and axiological changes are analyzed. It is determined that human freedom is the most important vector for the stable development of society in information stage. Freedom is seen in different dimensions. It is realized through justice, cooperation, safety of human life, which is guaranteed by an effective state.